NORMALIZATION OF LOAD THROUGH ACYCLIC EXERCISES IN PHYSICAL EDUCATION CLASSES OF ELEMENTARY SCHOOL STUDENTS OF GENERAL SECONDARY SCHOOLS (American Journal of Interdisciplinary Research and Development, 2022)
The article presents information about the measurement of the load in the course of classes by means of outdoor games in physical education lessons for younger schoolchildren